The Restructuring of the European Pharmaceutical Industry between 2000 and 2018 - Benedek Nagy (Comparative Economic Research. Central and Eastern Europe, 2021)
To meet the requirements of global competition, the European Union (EU) places particular emphasis on the development of knowledge-intensive, innovative industries. The pharmaceutical industry, as a high-tech manufacturing subsection, has a long tradition in Europe. However, the distribution of pharmaceutical industry employment and value added is not even within the Union, and its temporal dynamics is also different. In the present paper, I examine the change of the structure of the pharmaceutical industry within the Union using country groups. I compare the development of pharmaceutical industry employment in the period between 2000 and 2018 in three country groups. I use a simple decomposition method to separate the effects of sector growth and labor productivity change on the change of pharmaceutical employment to find out how similarly this industry evolved in the different country groups. The analysis shows that while in the 12 original, i.e., pre-2004, member states (Core EU), employment slightly increased alongside a considerable increase in value added, the nine post-socialist countries (PS9) achieved slightly greater value added expansion combined with substantial employment growth. Meanwhile, the four Visegrád countries (V4) achieved a value added growth similar to the PS9, but an even greater employment growth. This indicates that the part of the pharmaceutical industry operating with higher labor productivity is concentrating in the Core EU countries, while in the less developed post-socialist countries, the part of the pharmaceutical industry with lower labor productivity is developing.
Keywords: I18; L65; O14; 330; pharmaceutical industry; labor productivity; growth; Visegrád countries